PENGARUH PENGGUNAAN HANDPHONE BERBASIS ANDROID TERHADAP AKTIVITAS BELAJAR SISWA DI SD NEGERI 107826 PEMATANG SIJONAM - Eka Nadia Aprilia (PUSKAPAD, 2025)
The advancement of the era in the technological era has produced various sophisticated communication tools at affordable prices. The most popular communication tool today is a cellphone, especially the Android system. In its use, currently all levels of society are able to operate it, from children to adults. Elementary School 107826 Pematang Sijonam is one of the places affected by this technological advancement, this can be seen from the results of initial observations, where many of them are able to operate cellphones. The findings in the field made researchers want to see how the use of Android-based cellphones affects students' learning activities. The method used in this study is the correlational quantitative method. With the research subjects being 20 students of grade V of Elementary School 107826 Pematang Sijonam, using saturated sampling techniques as a sampling technique. And collecting data was taken using a questionnaire. Based on the results of the analysis, it was concluded that there was a significant influence between the use of Android-based cellphones on students' learning activities. The calculated “r” is 0.61584 with N = 20 on df 18 with a 5% significance level of 0.468 and a 1% significance level of 0.590, thus the calculated “r” is greater than the “r” table value (0.468 < 0.61584 > 0.590) this means that there is a relationship between variable X (the Effect of Using Android-Based Mobile Phones) and variable Y (student learning activities). The calculated t test is compared with the t table test for a 5% error of the two-tailed test and df = N – nr, df = 20 – 2 = 18. Then the t table = 1.734 can be obtained. If tcount 6.732 > ttable 1.734 then it shows that Ha (there is a significant influence between the use of android-based mobile phones on student learning activities at SD Negeri 107826 Pematang Sijonam) is accepted and there is Ho (there is no significant influence between the use of android-based mobile phones on student learning activities at SD Negeri 107826 Pematang Sijonam) is rejected.